Edible films and coatings as carriers of nano and microencapsulated ingredients - Guimarães, Ana Cristina Silva Esperança (2020)
Edible films and coatings can provide a protective barrier against physical and mechanical damage, as well as create a controlled atmosphere, by acting as a semi-permeable barrier for gases, vapor and water. These films and coatings also offer the possibility of incorporating different functional ingredients. Nevertheless, the incorporation of these functional compounds is not always easy and new technologies are needed for successful incorporation. One of the possibilities is the use of micro and nanoencapsulation technologies that could help adding the functional compounds by improving their stability and dispersibility, and at the same time decrease the adverse effects that they can have in the films and coatings' properties. This chapter aims to provide a comprehensive review of the use of edible films and coatings for the incorporation of functional ingredients for food applications.